Pengaruh Film Jumbo Terhadap Pemahaman Konsep Masalah Sosial Pada Anak Usia 5-6 Tahun Di TK Kartika II-3 Kota Palembang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effect of the animated film Jumbo on the understanding of social problem concepts among children aged 5-6 years at TK Kartika II-3 Palembang. The research used a quantitative one-group pretest-posttest design involving 15 children. Data were collected through structured observation sheets assessing three indicators: the ability to recognize problematic situations, identify causes and consequences, and provide simple solutions. The results showed a clear improvement after the intervention. The average pretest score was 12.53 and increased to 20.73 in the posttest, with a gain of 8.20 points. The Shapiro-Wilk test confirmed that both pretest (Sig. 0.071) and posttest (Sig. 0.239) were normally distributed. Hypothesis testing using the paired sample t-test showed a significance value of <0.001 with t = -13.575, indicating a highly significant difference between pretest and posttest scores. The research instrument also demonstrated high reliability with a Cronbach’s Alpha of 0.951. These findings confirm that the Jumbo film effectively enhances children’s understanding of social problems by presenting concrete visual situations that help them identify conflicts, understand cause-and-effect relationships, and express appropriate responses. The study concludes that the Jumbo film is a suitable audio-visual medium to support social learning and character development in early childhood education.